Presynchronizing PGF2α and GnRH injections before timed artificial insemination CO-Synch + CIDR program - Scott L. Hill; Stephanie Leeann Pulley; K. C. Olson; John R. Jaeger; Ryan M. Breiner; G.C. Lamb; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2013)
Fixed-time artificial insemination is an effective management tool that reduces the labor associated with more conventional artificial insemination programs requiring detection of estrus. The 7-day CO-Synch + controlled internal drug release (CIDR) insert protocol has been shown to effectively initiate estrus and ovulation in cycling and non-cycling suckled beef cows, producing pregnancy rates at or greater than 50% in beef cows. The gonadotropin-releasing hormone (GnRH) injection that begins the CO-Synch + CIDR program initiates ovulation in a large proportion of cows, particularly anestrous cows. The CIDR, which releases progesterone intravaginally, prevents short estrous cycles that usually follow the first postpartum ovulation in beef cows. Our hypothesis was that inducing estrus with a prostaglandin injection followed 3 days later with a GnRH injection, 7 days before applying the 7-day CO-Synch + CIDR protocol, might increase the percentage of cycling cows that would exhibit synchronous follicular waves after the onset of the CO-Synch + CIDR protocol. We also hypothesized that the additional GnRH injection would increase the percentage of anestrous cows that would ovulate, thereby increasing pregnancy outcomes.
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-162-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1083; Cattle; CIDR; GnRH; Timed artificial insemination; PGF2α; 7-day CO-Synch